(untitled) (Experimental biology, 2022)
Twenty-seven skulls of four subspecies of the common lynx (Lynx lynx Linnaeus, 1758): European (L. l. lynx L., 1758) (n = 2), Baikal (L. l. kozlovi Fetisov, 1950) (n = 2), Altai (L. l. wardi Lydekker, 1904) (n = 5) and Turkestan (L. l. isabellina Blyth, 1847) (n = 16) lynxes from nine different populations we studied. As a result of age analysis, among the skulls obtained, three were classified as juveniles, eight as subadult (up to 2-3 years), and 16 as adults. Ten variables were examined in the statistical data processing to compare the two sexes. The skulls of juveniles were not considered for statistical treatment due to their underdevelopment. Student t-test was used for comparing the means of variables, data analyzed were statistically significant at < 0.05. The overall dimensions of the skulls varied, and the males were comparatively larger than the females. The total length of the skull of males and females averaged 153.8 mm and 145.6 mm, respectively, while the zygomatic width of the skull in males averaged 108.6 mm and in females 102.8 mm. Similar differences in size were noted for the other 8 variables. A significant variation in the lynxes’ skulls size from different populations was noteworthy, which is presumably related to their body sizes. Thus, the skulls of the European and Altai lynx were larger than the skulls of the Turkestan to some degree. In the near future, we will need to look at more skulls from other populations and use more skull variables to study differences between populations and subspecies.